Evaluation, diagnosis, and treatment of shoulder injuries in athletes - Hudson, V. J. (Clinics in Sports Medicine, 2010)
The shoulder remains one of the more challenging joints for clinicians to clearly identify, diagnose, and treat within the athletic population. Its complexities involving the glenohumeral, acromioclavicular, sternoclavicular, and scapulothoracic joints moving in tandem require the physician and rehabilitation specialist to have a comprehensive understanding of the biomechanics and arthrokinematics associated with athletic activity. This chapter focuses on the evaluation, classification, mechanism of injury, and initial treatment of widespread shoulder injuries involved in sports.